Concurrent bloodstream infection with Lodderomyces elongisporus and Candida parapsilosis - Bryant Koh; Catriona Halliday; Raymond Chan (Medical Mycology Case Reports, 2020)
We report the case of a 54-year-old patient with central venous catheter related mixed candidaemia with Lodderomyces elongisporus and Candida parapsilosis, who responded to line removal and anidulafungin therapy.Mixed candidaemia was detected on Candida chromogenic agar. Identification of the two isolates was confirmed by MALDI-TOF MS (Bruker). Antifungal susceptibility testing revealed different antifungal MICs. This is the first reported case of mixed Lodderomyces candidaemia and outlines laboratory methodology to aid diagnosis and management.